2015
DOI: 10.2139/ssrn.2580856
|View full text |Cite
|
Sign up to set email alerts
|

Financial Illiteracy and Pension Contributions: A Field Experiment on Compound Interest in China

Abstract: This paper uses a field experiment to study the relationship between financial literacy and retirement savings in China. When the Chinese government launched a highly subsidized pension system in rural areas in 2009, 73% of households chose to save at a level that is lower than that implied by a benchmark life-cycle model. We test to what extent the low contribution level is due to a fundamental misunderstanding of the nature of compound interest. In a field experiment with more than 1000 Chinese households, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 25 publications
1
46
0
1
Order By: Relevance
“…Based on Sherraden et al (2001), Song (2012) and Bruhn et al (2014), we conclude that there is weak and furthermore mixed evidence about the value of delivering LTSI delivered to adults in a community setting. We further suggest that success or failure in this case may rest on the specific nature of the training and participants' willingness and ability to participate in timeconsuming activities during leisure hours (in contrast to workplace settings where the relevance is usually salient and the activity may be undertaken on the employers' time).…”
Section: Setting and Deliverymentioning
confidence: 66%
See 1 more Smart Citation
“…Based on Sherraden et al (2001), Song (2012) and Bruhn et al (2014), we conclude that there is weak and furthermore mixed evidence about the value of delivering LTSI delivered to adults in a community setting. We further suggest that success or failure in this case may rest on the specific nature of the training and participants' willingness and ability to participate in timeconsuming activities during leisure hours (in contrast to workplace settings where the relevance is usually salient and the activity may be undertaken on the employers' time).…”
Section: Setting and Deliverymentioning
confidence: 66%
“…In the context of farmer education, Song (2012) shows that more intensive financial education has significantly stronger effects on behaviour, particularly among older adults (although the longer version of the training also delivers additional content). Similarly, Doi et al (2012) also suggest that one potential explanation for why their financial training succeeds (versus other financial education programmes in similar contexts) may be due to the length (18 hours), although this is unlikely to be the only explanation given other important pedagogical differences.…”
Section: Duration and Frequencymentioning
confidence: 99%
“…• Non-product interventions that aim to change savings behavior: This includes "nudges" such as reminders to save, as well as financial education interventions Song, 2013). The use of each approach is often dependent on the constraints of the site for the field experimental evaluation.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…They also find some evidence that more-biased households save less in a representative sample of U.S. households. 24 Song (2013) tests the impact of financial education that focuses on compound interest with a field experiment that randomly assigned 1,104 households to one of three groups in Shaanxi province, China. One treatment group was taught principles of compound interest, with application to pension contributions and balances.…”
Section: Biases In Price Perceptions (Underestimating Compound Interest)mentioning
confidence: 99%
“…For example, Stango and Zinman (2009) have found that those with higher EGB "borrow more and save less" than less biased households. Additionally, Song (2012) finds in a Chinese field study that learning about compound interest can increase pension contributions by about 40%. Moreover, Levy and Tasoff (2015) find that eliminating EGB down from fully biased (i.e.…”
Section: "Compound Interest Is the Eighth Wonder Of The World He Whomentioning
confidence: 99%